Analisis Komunikasi Persuasif Visual dalam Promosi Event di Instagram @colorrunfestivalid - M. Teguh Dwi Rizki; Ali Alamsyah Kusumadinata; Nadia Amalia (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
This study examines the transformation of digital marketing communication that positions visual elements as the primary component in event promotion on social media, particularly Instagram. This shift is driven by changes in audience behavior, which has become more responsive to visual stimuli than to textual information. The research problem focuses on how visual elements are constructed as an effective persuasive communication strategy to capture attention, evoke emotions, and influence audience perceptions and interests through the peripheral route based on the Elaboration Likelihood Model framework. The study employs a qualitative approach using content analysis of 11 Instagram posts from @colorrunfestivalid selected through purposive sampling, supported by observation and interviews. The findings indicate that visual dominance reaches 82%, characterized by the use of bright colors, expressions of happiness, and interactive activities that effectively generate emotional appeal and rapid audience engagement. Most audiences pay greater attention to visuals than to text and demonstrate a willingness to participate after viewing the experiential representations presented. The psychological effect of fear of missing out further reinforces this response. The persuasion process is found to occur predominantly through the peripheral route, marked by low cognitive elaboration and a high reliance on visual cues. The study concludes that visuals function as the primary determinant of effective digital persuasive communication, as they simultaneously construct meaning, emotion, and experiential expectations. The novelty of this research lies in affirming visuals as the core of digital persuasion strategies through the integration of emotional, social, and psychological dimensions, while also reinforcing the dominance of the peripheral route as a key mechanism in contemporary media consumption.